Misoprostol versus uterine straightening by bladder distension for pain relief in postmenopausal patients undergoing diagnostic office hysteroscopy: a randomised controlled non-inferiority trial. (August 2016) - Fouda, Usama M.; Elshaer, Hesham S.; Elsetohy, Khaled A.; Youssef, Mohamed A.
Abstract: Objective: To compare the effectiveness of misoprostol with uterine straightening by bladder distension in minimising the pain experienced by postmenopausal patients during diagnostic office hysteroscopy. Study design: Seventy-six postmenopausal patients were randomly allocated in a 1:1 ratio to the misoprostol group or to the bladder distension group. Patients in the misoprostol group were instructed to insert two misoprostol tablets (400 μg) in the vagina 12 h before office hysteroscopy. Patients in the bladder distension group were instructed to drink one litre of water and to avoid urination during a period of 2 h before office hysteroscopy. The severity of pain experienced by the patients during and at 30 min after the procedure was measured using a 100-mm visual analogue scale (VAS). The ease of passing the hysteroscope through the cervical canal was assessed by the hysteroscopists using a 100-mm VAS. Results: The passage of the hysteroscope through the cervical canal was easier in the misoprostol group [60.37 ± 15.78 vs. 50.05 ± 19.88, p  = 0.015]. The mean VAS pain score during the procedure was significantly lower in the misoprostol group [39.47 ± 13.96 vs. 50.18 ± 15.44, p  = 0.002]. The mean VAS pain score 30 min post-procedure was comparable between both groups [11.82 ± 3.71 vs. 12.61 ± 4.06, p  = 0.379]. Conclusion: Vaginal misoprostol is more effective than uterine straightening by bladder distension in relieving the pain experienced by postmenopausal patients during office hysteroscopy. Trial registration: Clinicaltrials.gov [NCT02328495].https://clinicaltrials.gov/ct2/show/NCT02328495 .